Perioperative Chemotherapy or Preoperative Chemoradiotherapy in Esophageal Cancer - Hoeppner, Jens; Brunner, Thomas; Schmoor, Claudia; Bronsert, Peter; Kulemann, Birte; Claus, Rainer; Utzolino, Stefan; Izbicki, Jakob Robert; Gockel, Ines; Gerdes, Berthold; Ghadimi, Michael; Reichert, Benedikt; et al. (New England Journal of Medicine, 2025)
Background The best multimodal approach for resectable locally advanced esophageal adenocarcinoma is unclear. An important question is whether perioperative chemotherapy is preferable to preoperative chemoradiotherapy. Methods In this phase 3, multicenter, randomized trial, we assigned in a 1:1 ratio patients with resectable esophageal adenocarcinoma to receive perioperative chemotherapy with FLOT (fluorouracil, leucovorin, oxaliplatin, and docetaxel) plus surgery or preoperative chemoradiotherapy (radiotherapy at a dose of 41.4 Gy and carboplatin and paclitaxel) plus surgery. Eligibility criteria included a primary tumor with a clinical stage of cT1 cN+, cT2-4a cN+, or cT2-4a cN0 disease, in which T indicates the size and extent of the tumor (higher numbers indicate a more advanced tumor), and N indicates the presence (N+) or absence (N0) of cancer spread to the lymph nodes, without evidence of metastatic spread. The primary end point was overall survival. Results From February 2016 through April 2020, we assigned 221 patients to the FLOT group and 217 patients to the preoperative-chemoradiotherapy group. With a median follow-up of 55 months, overall survival at 3 years was 57.4% (95% confidence interval [CI], 50.1 to 64.0) in the FLOT group and 50.7% (95% CI, 43.5 to 57.5) in the preoperative-chemoradiotherapy group (hazard ratio for death, 0.70; 95% CI, 0.53 to 0.92; P=0.01). Progression-free survival at 3 years was 51.6% (95% CI, 44.3 to 58.4) in the FLOT group and 35.0% (95% CI, 28.4 to 41.7) in the preoperative-chemoradiotherapy group (hazard ratio for disease progression or death, 0.66; 95% CI, 0.51 to 0.85). Among the patients who started the assigned treatment, grade 3 or higher adverse events were observed in 120 of 207 patients (58.0%) in the FLOT group and in 98 of 196 patients (50.0%) in the preoperative-chemoradiotherapy group. Serious adverse events were observed in 98 of 207 patients (47.3%) in the FLOT group and in 82 of 196 patients (41.8%) in the preoperative-chemoradiotherapy group. Mortality at 90 days after surgery was 3.1% in the FLOT group and 5.6% in the preoperative-chemoradiotherapy group. Conclusions Perioperative chemotherapy with FLOT led to improved survival among patients with resectable esophageal adenocarcinoma as compared with preoperative chemoradiotherapy.
CRIS-Team Scopus Importer:2025-02-28
Keywords: Gastroenterology; Gastrointestinal Tract Cancer; Gastrointestinal Tract Cancer; Hematology/Oncology; Treatments in Oncology